2018
DOI: 10.1177/1521025118796633
|View full text |Cite
|
Sign up to set email alerts
|

It Was Really Tough”—Exploring the Feelings of Isolation and Cultural Dissonance With Black American Males at a Predominantly White Institution

Abstract: Black American males and low socioeconomic status students face a gauntlet of obstacles when pursuing their college degrees. These young men do not earn degrees at the same rate as their peers. As campus engagement, recreation, and leisure play pivotal roles in students’ experiences, investigating their influence relative to social integration might facilitate a better understanding of the issues they face. This study explored how Black American male undergraduates from low socioeconomic status backgrounds per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…internships, student organizations, study abroad; Strayhorn, 2011). However, some studies have found that the community built and the social interactions that transpire during bridge programs provide students with an unrealistic understanding of what the college environment will be like post-program (Patterson, 2018). This is especially true for students of color at predominantly White institutions (Patterson, 2018).…”
Section: Social Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…internships, student organizations, study abroad; Strayhorn, 2011). However, some studies have found that the community built and the social interactions that transpire during bridge programs provide students with an unrealistic understanding of what the college environment will be like post-program (Patterson, 2018). This is especially true for students of color at predominantly White institutions (Patterson, 2018).…”
Section: Social Interactionsmentioning
confidence: 99%
“…However, some studies have found that the community built and the social interactions that transpire during bridge programs provide students with an unrealistic understanding of what the college environment will be like post-program (Patterson, 2018). This is especially true for students of color at predominantly White institutions (Patterson, 2018). In a study of Black American males at a predominantly White institution, Patterson (2018) found that those who were involved in an educational opportunity program in the summer before their fall semester struggled in the fall because they did not feel connected to the broader campus community.…”
Section: Social Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, students of color use peer-to-peer networks among freshmen to improve their academic performance and navigate college life. Peer networks are essential in improving underrepresented racial minority students campus engagement, recreation, and leisure, which play important roles in their social integration (Farmer-Hinton, 2008;Patterson, 2018;Zirkel, 2004). We thus hypothesized that FIGs, which are intentionally designed to build mentoring relationships and learning social and academic learning support, may be particularly beneficial for underrepresented racial minority students.…”
Section: Propensity Score Matchingmentioning
confidence: 99%
“…In addition, they did not account for other factors that affect student retention, such as racial identity (Patterson, Preuss, Bennett, Renner, & Wanstreet 2 2021;Rodriguez & Mallinckrodt, 2021;Strayhorn, 2013;and Toven-Lindsey et al, 2015), age (Ahn & Davis, 2020), gender (Kelly et al, 2021;and Patterson, 2021), first-generation status (Radunzel, 2021;Manyanga et al, 2017;and Donaldson et al, 2016), time to degree (Yue & Fu, 2017), math or English remediation (Boatman, 2021), transfer credits (Boston et al, 2011), or financial issues (Ellis, 2017;Manyanga et al, 2017;and Braxton et al, 2007).…”
Section: Introductionmentioning
confidence: 99%